2021
DOI: 10.1002/jsfa.11704
|View full text |Cite
|
Sign up to set email alerts
|

Whole wheat bread enriched with silver fir (Abies alba Mill.) needles extract: technological and antioxidant properties

Abstract: BACKGROUND: The interest of consumers and market and scientific research for added-value foods obtained with environmentally sustainable productive chains is increasing. Silver fir (Abies alba Mill.) needles (SFNs), often by-products of forest management and logging, represent an unexploited source of bioactive compounds. RESULTS: For the first time, SFN aqueous extract obtained through controlled hydrodynamic cavitation was used to enrich whole wheat flour bread. The first trial found that 35% SFNs extract ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
(161 reference statements)
0
2
0
Order By: Relevance
“…Its usage for consumption started over a century ago in the production of, for example, silver fir beer [2]. It is a medicinal plant that is used in the food, health products, pharmaceuticals and cosmetics industries [3][4][5]. Research and publications provide scientific evidence to support claims that silver fir phytochemicals provide health benefits to consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Its usage for consumption started over a century ago in the production of, for example, silver fir beer [2]. It is a medicinal plant that is used in the food, health products, pharmaceuticals and cosmetics industries [3][4][5]. Research and publications provide scientific evidence to support claims that silver fir phytochemicals provide health benefits to consumers.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that this polysaccharide could serve as a potential antioxidant agent for developing functional foods [105]. Furthermore, aqueous extracts obtained through cavitation have been successfully incorporated into bread, resulting in value-added and functional bread products [110]. Aqueous extracts obtained both from fresh and dried pine needles (Pinus densiflora) exhibit significant reductive power, inhibition of lipid peroxidation, and the ability to scavenge free radicals, comparable to those of known antioxidants-phenolic compounds.…”
Section: Preparation and Properties Of Aqueous Extractsmentioning
confidence: 99%
“…The use of extracts obtained using HC in consumer goods has been tested, for example, in gluten-free biscuits supplemented with a pectin-based compound extracted from waste lemon peel [ 33 ] and whole-wheat bread supplemented with an extract from silver fir needles [ 34 ]. However, the technological properties of these extracts have never been investigated.…”
Section: Introductionmentioning
confidence: 99%